2022
DOI: 10.1101/2022.07.20.500837
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction error neurons in mouse cortex are molecularly targetable cell types

Abstract: Predictive processing postulates the existence of prediction error neurons in cortex. Functionally, both negative and positive prediction error neurons have been identified in layer 2/3 of visual cortex, but whether they correspond to transcriptionally defined subpopulations is unclear. Here we used the activity-dependent, photoconvertible marker CaMPARI2 to tag neurons in layer 2/3 of visual cortex during stimuli and behaviors designed to trigger prediction errors. We performed single-cell RNA-sequencing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…More generally, the distinct inhibitory environments of upper and lower layer 2/3 have been observed across the brain, from primary sensory cortices 43,77 to higher-order association areas 78 , suggesting that it may reflect a general functional specialization. For example, the distinct inhibitory environments of layer 2 and layer 3 are potentially well-posed for differential inhibition of top-down versus sensory-driven activity that has been recently described 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…More generally, the distinct inhibitory environments of upper and lower layer 2/3 have been observed across the brain, from primary sensory cortices 43,77 to higher-order association areas 78 , suggesting that it may reflect a general functional specialization. For example, the distinct inhibitory environments of layer 2 and layer 3 are potentially well-posed for differential inhibition of top-down versus sensory-driven activity that has been recently described 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent experimental study suggested that positive and negative prediction-error neurons in L2/3 map to different transcriptomically defined cell types [28]. If that is correct, then one can expect the above mentioned connectivity differences between these classes – namely, prominent differences in inputs to the different classes of L2/3 neurons from, e.g., L4, but less difference in recurrent connections in L2/3.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that in V1, L2/3 PyCs indeed respond to mismatches between visual flow and locomotion 7,[52][53][54] . Recent evidence suggests that two genetically defined subpopulations of L2/3 PyCs preferentially respond to (unexpected) visual stimuli, which could be considered positive prediction errors, or visuomotor mismatch, which could be seen as negative prediction errors 51 . In line with these findings, we observed two functional clusters of PyCs in L2/3, one responding predominantly to visual stimuli (V-PyCs) and the other to visuomotor mismatch (NV-PyCs).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that a significant fraction of V1 PyCs exhibit strong visuomotor mismatch responses when the visual flow of the tunnel is abruptly stopped while the mice are still running 7,[51][52][53][54][55][56] . Recent evidence suggests that PyCs with visuomotor mismatch responses may belong to a genetically distinct subpopulation that is less visually responsive 51 . Therefore, we assessed whether the two populations of PyCs we identified also differed in terms of their visuomotor mismatch responses.…”
Section: Chcs Have Similar Response Properties As Non-visual Pycsmentioning
confidence: 99%